Barriers to Accessing Kidney Transplantation Among Populations Marginalized by Race and Ethnicity in Canada: A Scoping Review Part 1—Indigenous Communities in Canada. (March 2021) - El-Dassouki, Noor; Wong, Dorothy; Toews, Deanna M.; Gill, Jagbir; Edwards, Beth; Orchanian-Cheff, Ani; Smith, Mary; Neves, Paula; Marshall, Lydia-Joi; Mucsi, Istvan
Background: Kidney transplantation (KT), a treatment option for end-stage kidney disease (ESKD), is associated with longer survival and improved quality of life compared with dialysis. Inequities in access to KT, and specifically, living donor kidney transplantation (LDKT), have been documented in Canada along various demographic dimensions. In this article, we review existing evidence about inequitable access and barriers to KT and LDKT for patients from Indigenous communities in Canada. Objective: To characterize the current state of literature on access to KT and LDKT among Indigenous communities in Canada and to answer the research question, "what factors may influence inequitable access to KT among Indigenous communities in Canada." Eligibility criteria: Databases and gray literature were searched in June and November 2020 for full-text original research articles or gray literature resources addressing KT access or barriers in Indigenous communities in Canada. A total of 26 articles were analyzed thematically. Sources of evidence: Gray literature and CINAHL, OVID Medline, OVID Embase, and Cochrane databases. Charting methods: Literature characteristics were recorded and findings which described rates of and factors that influence access to KT were summarized in a narrative account. Key themes were subsequently identified and synthesized thematically in the review. Results: Indigenous communities in Canada experience various barriers in accessing culturally safe medical information and care, resulting in inequitable access to KT. Barriers include insufficient incorporation of Indigenous ways of knowing and being in information dissemination and care for ESKD and KT, spiritual concerns, health beliefs, logistical hurdles to accessing care, and systemic mistrust resulting from colonialism and systemic racism. Limitations: This review included studies that used various methodologies and did not assess study quality. Data on Indigenous status were not reported or defined in a standardized manner. Indigenous communities are not homogeneous and views on organ donation and KT vary by individual. Conclusions: Our scoping review has identified potential barriers that Indigenous communities may face in accessing KT and LDKT. Further research is urgently needed to better understand barriers and support needs and to develop strategies to improve equitable access to KT and LDKT for Indigenous populations in Canada.